Silicon fertigation and salicylic acid foliar spraying mitigate ammonium deficiency and toxicity in Eucalyptus spp. clonal seedlings - de Souza, Jonas Pereira [UNESP] (2021)
Nitrogen deficiency and toxicity, primarily in its ammonium form (NH4+), can suppress plant growth and development. The use of silicon (Si) or salicylic acid (SA) may be an alternative to minimize the harmful effects of nutrient imbalances caused by NH4+, thereby improving the photosynthetic efficiency of plants. The aim of the present study was to assess the action of fertigation-applied Si and SA foliar spraying in mitigating NH4+ toxicity and deficiency in eucalyptus clonal seedlings. Two experiments were performed with eucalyptus clonal seedlings (Eucalyptus urophylla x Eucalyptus grandis), in a greenhouse. Both were carried out using a 4x2 factorial design and four concentrations of NH4+ (5, 15, 30 and 60 mmol L-1), in the absence and presence of Si (2 mmol L-1), in experiment I; or with and without SA foliar application (10−2 mmol L-1), in experiment II, with six repetitions. Nitrogen content rose as a result of increasing N-NH4+ concentration in the nutrient solution, and Si supplied via the nutrient solution was efficient in increasing the Si content in eucalyptus seedlings. The rise in N-NH4+ concentration favored the maintenance of the photosynthetic apparatus, but high N-NH4+ concentration increased energy loss through fluorescence and decreased the efficiency of photosystem II. The addition of Si to the nutrient solution proved to be beneficial to the photosynthetic apparatus by decreasing F0 at 15 and 30 mmol L-1 of NH4+; and Fm at all NH4+ concentrations studied. In addition, the beneficial element also increases Fv/Fm at all NH4+ concentrations studied. SA foliar application was also efficient in reducing photosynthetic energy losses by decreasing F0 and Fm at all NH4+ concentrations studied. However, SA only increased the Fv/Fm at the high concentrations studied (30 and 60 mmol L-1 of NH4+). Nitrogen disorder by deficiency or N-NH4+ toxicity reduced shoot dry mass production. The addition of Si to the nutrient solution and SA foliar application increased shoot dry mass production at all N-NH4+ concentrations studied, and benefitted the photosynthetic apparatus by decreasing fluorescence and improving the quantum efficiency of photosystem II as well as dry mass production.